Pemikiran Pendidikan Islam Ibn Miskawaih (Studi tentang Konsep Akhlak dan Korelasinya dengan Sistem Pendidikan) - Matanari, Ratimah (Al-Fikru: Jurnal Ilmiah, 2021)
The current education is far from expectations, it can be seen from the failure of Islamic educational institutions in producing a generation with good morals. Actually there are many concepts presented by previous figures, including Ibn Miskwaih. On this basis, this study aims to analyze Ibn Miskawaih's thoughts on moral education and the education system. The research method used is library research. The primary data used is the book of Tahdzib al-Akhlak. secondary data obtained from other books, and articles sourced from journals and research results. The results of the study explain that humans consist of physical and spiritual and have the potential or basic abilities that are tabi'i, but they can change due to influences from within and outside of humans, namely through education. Ibn Miskawaih hints that the purpose of education is the formation of a noble personality, which he calls isabah al-khuluq al-syrif, namely a substantially and essential noble person, not a temporal and accidental glory such as a materialistic and autocratic person. While the educational methods and tools that can be used according to Ibn Miskawaih are natural methods (tabi'i), advice and guidance, threats of rebuke, blows and punishments, flattery and praise, and educating based on educational principles.